Pertanggung Jawaban Hukum terhadap Anak Penyandang Disabilitas Sebagai Korban Kekerasan Seksual di Lingkungan Keluarga: indonesia - Petrus Kanisius I Kadek Hengky Adi Putra; A.A.A Ngurah Tini Rusmini Gorda; Ni Nyoman Juwita Arsawati; Komang Satria Wibawa Putra (AKADEMIK: Jurnal Mahasiswa Humanis, 2026)
Sexual violence against children with disabilities within the family remains a hidden and persistent human rights violation, exacerbated by unequal power relations and the victims’ physical, intellectual, or sensory limitations. This study aims to examine the legal responsibility for sexual violence against children with disabilities in the family environment and to assess the implementation of victims’ rights under Law Number 8 of 2016 on Persons with Disabilities, Law Number 35 of 2014 on Child Protection, and Law Number 12 of 2022 on the Crime of Sexual Violence. Employing normative legal research, this study analyzes statutory regulations, legal doctrines, and relevant secondary legal materials. The findings indicate that although Indonesian law provides a comprehensive framework for criminal liability and victim protection, its implementation remains ineffective due to limited accessibility, insufficient accommodation for persons with disabilities, and weak victim-oriented procedures in the criminal justice process. The study contributes by emphasizing the necessity of disability-sensitive legal mechanisms, particularly in reporting, investigation, and victim recovery, to prevent secondary victimization and ensure substantive justice for children with disabilities.